Adult pulmonary blastoma in an adult with urothelial cancer: A case report. (2021) - Kolekar, Shailesh; Gudmundsdottir, Kristrun; Olsen, Karen Ege; Sivapalan, Pradeesh; Clementsen, Paul Frost; Bodtger, Uffe
Abstract: Pulmonary blastoma is an aggressive lung cancer with incidence ranging from 0.25–0.5 of all the reported lung cancers. Although, pulmonary blastoma is seen commonly in childhood its very rare in adults. Surgical treatment is often the treatment of choice, but benefits of neoadjuvant chemotherapy are unclear. People with DICER1 syndrome commonly develop Pulmonary blastoma and do have concomitant or previous history of benign or malignant tumours in extra pulmonary site like kidney, thyroid, ovary cervix testicle and eye. As per our knowledge, this is the first case of adult pulmonary blastoma previously diagnosed with urothelial cancer and a strong familial predilection of malignancy, with negative genetic test for DICER1 mutations.